Lime powder treatment reduces urinary excretion of total protein and transferrin but increases uromodulin excretion in patients with urolithiasis - Tosukhowong, Piyaratana; Kulpradit, Pimsuda; Chaiyarit, Sakdithep; Ungjareonwattana, Wattanachai; Kalpongnukul, Nuttiya; Ratchanon, Supoj; Thongboonkerd, Visith (Urolithiasis, 2018)
Our previous study has shown that lime powder (LP) had an inhibitory effect against calcium oxalate stone formation. However, the precise mechanisms underlying such beneficial effect remained unclear. Our present study thus aimed to address the effect of LP on excretory level and compositions of urinary proteins using a proteomics approach. From a total of 80 calcium oxalate stone formers recruited into our 2-year randomized clinical trial of LP effect, 10 patients with comparable age and clinical parameters were selected for this proteomic study. 24-h urine specimens were collected from all subjects, at baseline (before) and after LP treatment for 6 months, and then subjected to quantitative proteomics analysis and subsequent validation by ELISA. Total urinary protein excretion was significantly decreased by LP treatment, but unaffected by placebo. Nanoflow liquid chromatography coupled to tandem mass spectrometry (nanoLC–MS/MS) followed by quantitative analysis revealed 17 proteins whose levels were significantly altered (16 decreased and 1 increased) exclusively by LP treatment. Among these, the decrease of transferrin and increase of uromodulin were validated by ELISA. Moreover, there was a significant correlation between microalbuminuria and urinary transferrin level by Pearson’s correlation test. In summary, LP treatment caused significant reduction in total urinary protein excretion and changes in urinary protein compositions that could be linked to stone inhibitory effects and might be relevant mechanisms responsible for the beneficial effects of LP to prevent kidney stone formation and recurrence.